Penerapan Keadilan Restoratif terhadap Penyelesaian Tindak Pidana Penggelapan dan Penipuan (Studi di Polda Jatim) - Rafli Hamzan Aryaputra; Hervina Puspitosari (CV Rewang Rencang, 2025)
Restorative justice is recognized in the criminal law system. Its primary goal is to resolve cases while respecting the values of justice for all parties involved. Restorative justice can be applied to minor to moderate crimes, such as embezzlement and fraud. Embezzlement and fraud are common crimes that frequently occur, causing grief in society. The results of this study are the implementation of settlement mechanisms and standard operating procedures for the implementation of restorative justice. Barriers to the implementation of restorative justice include a lack of police personnel, difficulty for the parties to reach an agreement, and not all cases qualifying for restorative justice.